Ações investigativas e colaborativas no processo de formação de professores e nas práticas em educação infantil - Segat, Taciana Camera (2002)
This work describes and analyses a collaborative and reflexive process of teacher education for child education in the municipality of Santa Maria, Rio Grande do Sul State, Brazil. During two years, in a collaborative and dialectic process, we work with future teachers and teachers of child education, in schools and in University (UFSM). We attempt to rebuild the curriculum, by a critical analysis of our practices, considering teachers and future teachers as transformative professional in schools.